Agricultural innovation systems : an investment sourcebook - World Bank (Washington, DC : The World Bank, 2012)
Managing the ability of agriculture to meet rising global demand and to respond to the changes and opportunities will require good policy, sustained investments, and innovation - not business as usual. Investments in public Research and Development, extension, education, and their links with one another have elicited high returns and pro-poor growth, but these investments alone will not elicit innovation at the pace or on the scale required by the intensifying and proliferating challenges confronting agriculture. Experience indicates that aside from a strong capacity in Research and Development, the ability to innovate is often related to collective action, coordination, the exchange of knowledge among diverse actors, the incentives and resources available to form partnerships and develop businesses, and conditions that make it possible for farmers or entrepreneurs to use the innovations. While consensus is developing about what is meant by 'innovation' and 'innovation system', no detailed blueprint exists for making agricultural innovation happen at a given time, in a given place, for a given result. The AIS approach that looks at these multiple conditions and relationships that promote innovation in agriculture, has however moved from a concept to a sub-discipline with principles of analysis and action. AIS investments must be specific to the context, responding to the stage of development in a particular country and agricultural sector, especially the AIS. This sourcebook contributes to identifying, designing, and implementing the investments, approaches, and complementary interventions that appear most likely to strengthen AIS and to promote agricultural innovation and equitable growth. It emphasizes the lessons learned, benefits and impacts, implementation issues, and prospects for replicating or expanding successful practices. The information in this sourcebook derives from approaches that have been tested at different scales in different contexts. It reflects the experiences and evolving understanding of numerous individuals and organizations concerned with agricultural innovation, including the World Bank. This information is targeted to the key operational staff in international and regional development agencies and national governments who design and implement lending projects and to the practitioners who design thematic programs and technical assistance packages. The sourcebook can also be an important resource for the research community and nongovernmental organizations (NGOs)
1. Coordination and collective action for agricultural innovation -- 2. Agricultural education and training to support agricultural innovation systems -- 3. Investment in extension and advisory services as part of agricultural innovation systems -- 4. Agricultural research within an agricultural innovation systems -- 5. Incentives and resources for innovation partnerships and business development -- 6. Creating an enabling environment for agricultural innovation -- 7. Assessing, priotizing, monitoring, and evaluating agricultural innovation systems
Includes bibliographical references and index
Keywords: Agricultural innovation -- Economic aspects; Agriculture -- Economic aspects; Rural development